Case Settlement of Protected Forest Destruction Case in Ranca Upas Based on Law Number 41 Year 1999 on Forestry - Fajar, Muhamad Ibnu (Proceedings Series on Social Sciences & Humanities, 2023)
In Article 50 paragraph (2) of Law Number 41 of 1999 concerning Forestry, every person who is granted a business license for the utilization of environmental services, a business license for the ultilization of timber and non – timber forest products, and a license to collect timber and non – timber forest products, is prohibited from carrying out activities that cause forest damage. The violation of the article is in the Rancaupas area, Rancabali District, Bandung Regency where the damage to the protected forest is caused by a trail event (Camping Adventure Explore) which damages one of the flora protected by the government in the form of Edelweiss swamp flowers. The purpose of this research is to find the settlement point of the Rancaupas conservation forest damage case and what are the responsibilities of the Rancaupas protected forest damage. The research method used by the author is a normative juridical approach with this method to find a rule of law, legal principles, and legal doctrines to answer the legal doctrines to answer the legal issues at hand. The results of the study are in the form of a solution to the damage in the protected forest of Ranca Upas by securing the event organizers and following up into the realm of law. As well as responsibility for the damage to the protected forest in Ranca Upas by conducting joint rehabilitation, namely the government, Perhutani,the community and also the event organizer.